Association Between DNA Damage Response, Fibrosis and Type I Interferon Signature in Systemic Sclerosis - Vlachogiannis, Nikolaos I.; Pappa, Maria; Ntouros, Panagiotis A.; Nezos, Adrianos; Mavragani, Clio P.; Souliotis, Vassilis L.; Sfikakis, Petros P. (Frontiers in Immunology, 2020)
Increased endogenous DNA damage and type I interferon pathway activation have been implicated in Systemic Sclerosis (SSc) pathogenesis. Since experimental evidence suggests an interplay between DNA damage response/repair (DDR/R) and immune response, we hypothesized that deregulated DDR/R is associated with type I interferon signature and/or fibrosis extent in SSc. DNA damage levels, oxidative stress, induction of abasic sites and the efficiency of DNA double-strand breaks repair (DSB/R) and nucleotide excision repair (NER) were assessed in peripheral blood mononuclear cells (PBMCs) derived from 37 SSc patients and 55 healthy controls; expression of DDR/R-associated genes and type I interferon-induced genes was also quantified. Endogenous DNA damage was significantly higher in untreated diffuse or limited SSc (Olive Tail Moment; 14.7±7.0 and 9.5±4.1, respectively), as well as in patients under cytotoxic treatment (15.0±5.4), but not in very-early-onset SSc (5.6±1.2) compared with controls (4.9±2.6). Moreover, patients with pulmonary fibrosis had significantly higher DNA damage levels than those without (12.6±5.8 vs 8.8±4.8, respectively). SSc patients displayed increased oxidative stress and abasic sites, defective DSB/R but not NER capacity, downregulation of genes involved in DSB/R (MRE11A, PRKDC) and base excision repair (PARP1, XRCC1), and upregulation of apoptosis-related genes (BAX, BBC3). Individual levels of DNA damage in SSc PBMCs correlated significantly with the corresponding mRNA expression of type I interferon-induced genes (IFIT1, IFI44 and MX1, r=0.419-0.490), as well as with corresponding skin involvement extent, by modified Rodnan skin scores (r=0.481). In conclusion, defective DDR/R may exert a fuel-on-fire effect on type-I interferon pathway activation and contribute to tissue fibrosis in SSc.